1995
DOI: 10.1007/bf00229856
|View full text |Cite
|
Sign up to set email alerts
|

Different patterns of fore-hindlimb coordination during overground locomotion in cats with ventral and lateral spinal lesions

Abstract: The effect of large, low thoracic (T10-T11), partial spinal lesions involving the ventral quadrants of the spinal cord and, to a different extent, the dorsolateral funiculi, on fore-hindlimb coordination was examined in cats walking overground at moderate speeds (40-100 cm/s). Three different forms of impairment of fore-hindlimb coordination depending on the extent of the lesions, were observed. Lesions sparing the dorsolateral or the ventral funiculus on one side preserved the equality of the fore- and hindli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 23 publications
2
36
0
1
Order By: Relevance
“…Dorsolateral pathways. Cats can walk over ground after large lesions of the dorsolateral white matter (Gorska et al 1993b;Zmyslowski et al 1993;Bem et al 1995). In more quantitative studies of treadmill locomotion after lesions of the dorsolateral funiculus, which included the dorsal columns , it was shown that voluntary quadrupedal locomotion is impaired for 3-10 days.…”
Section: Functional Locomotor Recovery After Spinal Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dorsolateral pathways. Cats can walk over ground after large lesions of the dorsolateral white matter (Gorska et al 1993b;Zmyslowski et al 1993;Bem et al 1995). In more quantitative studies of treadmill locomotion after lesions of the dorsolateral funiculus, which included the dorsal columns , it was shown that voluntary quadrupedal locomotion is impaired for 3-10 days.…”
Section: Functional Locomotor Recovery After Spinal Lesionsmentioning
confidence: 99%
“…For locomotion to recover, a small part of a ventrolateral quadrant had to be spared (Afelt 1974;Eidelberg et al 1981a,b;Contamin 1983). However, other experiments suggested that cats (Gorska et al 1990(Gorska et al , 1993aZmyslowski et al 1993;Bem et al 1995;Rossignol et al 1999) and monkeys (Vilensky et al 1992) could walk with the hindlimbs even after large lesions of these pathways at the last thoracic segment (T13). Similarly, humans who had a surgical section of ventral pathways for intractable pain retained walking ability (Nathan 1994).…”
Section: Functional Locomotor Recovery After Spinal Lesionsmentioning
confidence: 99%
“…Furthermore, propriospinal fibers connecting the forelimb and hindlimb enlargements have been demonstrated in the ventral and/or ventrolateral white matter in turtles (Kusuma and ten Donkelaar 1980), cats (Giovanelli Barilari and Kuypers 1969), and rats (Reed et al 2006), indicating likely locations of axons contributing to interlimb phase control. Other studies in cats (Bem et al 1995;Brustein and Rossignol 1998;Gorska et al 1993aGorska et al ,b, 1996Jiang and Drew 1996;Kato 1992;Zmyslowski et al 1993) and rats (Loy et al 2002a,b;Schucht et al 2002) assessed the effects of spinal lesions on forelimb-hindlimb coordination, suggesting that both the DLF and VLF contained axons contributing to interlimb coupling.…”
Section: Introductionmentioning
confidence: 98%
“…Lesion to this structure or to the reticulospinal pathways, in both cats and primates, leads to an inability to maintain an upright posture during normal everyday activities (Kuypers 1963;Lawrence and Kuypers 1968a,b) including locomotion (Afelt 1974;Bem et al 1995;Brustein and Rossignol 1998;Górska et al 1990Górska et al , 1993Górska et al , 1995. The deficits that are observed following such lesions are widespread and normally include a loss of control over all four limbs as well as of axial musculature.…”
Section: Introductionmentioning
confidence: 99%